Does Money Supply and Oil Price Drive Inflation in ASEAN - Ulfah, Nadia; Subardin, Muhammad; Igamo, Alghifari Mahdi; Gustriani, Gustriani (Moneter: Jurnal Keuangan dan Perbankan, 2024)
Developing countries in Southeast Asia are countries that have economic problems such as inflation. This study aims to examine the effect of the money supply, exchange rates, and oil prices on inflation in ASEAN countries. Using panel data, this study consists of six countries in ASEAN namely Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam during the period 2001-2020. The analysis using Random Effect Model method shows that the money supply and world oil prices have a positive and significant effect on inflation in the six ASEAN countries. Meanwhile, the exchange rate variable has a positive but not significant effect on inflation in the six ASEAN countries. The central bank should control and reduce the growth rate of the money supply and the government should implement steps to reduce dependence on oil so as to help reduce the impact of rising oil prices on inflation.